1978
DOI: 10.1084/jem.148.4.1052
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lactoferrin as the granulocyte-derived inhibitor of colony-stimulating activity production.

Abstract: Lactoferrin (LF), the iron-binding protein present in the specific granules of mature granulocytes has been identified as colony inhibitory factor (CIF) which suppresses granulocyte--macrophage colony stimulating activity (CSA) production by monocytes and macrophages in vitro and rebound granulopoiesis in vivo. Separation of LF and CIF by isoelectric focusing confirmed that the regions of inhibitory activity corresponded in both to a pH of congruent to 6.5. In addition, the purified immunoglobulin fraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(73 citation statements)
references
References 31 publications
0
73
0
Order By: Relevance
“…We cannot exclude the possibility that a subpopulation of lymphoid, granulocytic or tumour cells which also adhere might play an accessory role in this growth-stimulatory process. It is possible that tumour cells produce colony-stimulating activity (CSA) (Okabe et al, 1978) which has been shown to be capable of influencing prostaglandin E production (Kurland et al, 1979) and, furthermore, contaminating polymorphonuclear leucocytes can affect CSA by release of lactoferrin (Broxmeyer et al, 1978). However, it has previously been reported that phagocytic depletion alone (which would not remove lymphoid cells) markedly reduces tumour-colony growth (Hamburger et al, 1978) reinforcing the central regulatory role of the macrophage.…”
Section: Methodsmentioning
confidence: 99%
“…We cannot exclude the possibility that a subpopulation of lymphoid, granulocytic or tumour cells which also adhere might play an accessory role in this growth-stimulatory process. It is possible that tumour cells produce colony-stimulating activity (CSA) (Okabe et al, 1978) which has been shown to be capable of influencing prostaglandin E production (Kurland et al, 1979) and, furthermore, contaminating polymorphonuclear leucocytes can affect CSA by release of lactoferrin (Broxmeyer et al, 1978). However, it has previously been reported that phagocytic depletion alone (which would not remove lymphoid cells) markedly reduces tumour-colony growth (Hamburger et al, 1978) reinforcing the central regulatory role of the macrophage.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, C/EBP⑀ induces the expression of target genes such as lactoferrin in mature granulocytes which may be involved in the negative (feedback) regulation of myelopoiesis. 12,13 The bone marrow morphology of C/EBP⑀ −/− mice suggested the coexistence of increased proliferation and apoptosis, with nearly 100% cellularity on biopsy specimen of the marrow and prominent pseudo-Gaucher cells throughhout the marrow. We, therefore, investigated whether myeloid cells in C/EBP⑀ −/− mice show abnormalities in their proliferative behavior in vivo and in vitro as well as in their response to apoptotic stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…14 19 However, LTF exerts various immunomodulatory effects in monocytes, macrophages and neutrophils 17 and may affect myelopoiesis. 20,21 A membrane-bound form of LTF (CSP82) has been implicated in regulating dendritic development in vitro and in vivo. 22 In a search for myeloid-specific markers that are absent from HSCs, lymphoid and erythroid cells, we analyzed the expression pattern of Ltf during hematopoietic development.…”
Section: Introductionmentioning
confidence: 99%